PROMOTIONAL STRATEGY OF KORNER CIRCLE K IN FACING RTE MINIMARKET COMPETITION - Nur Bany, Maulyna; Rusdianto, R. Yuniardi (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2026)
This study analyzes the promotional strategy of Korner Circle K in facing Ready-to-Eat (RTE) product competition from minimarkets in the Educity Harvard Pakuwon City Surabaya area. The rapid growth of modern retail in Indonesia has intensified competition between convenience stores and conventional minimarkets, making effective promotional strategy crucial for business sustainability. Using qualitative methods with a case study approach, data were collected through in-depth interviews with 7 informants: 1 key informant (store manager), 2 primary informants (staff), and 4 supporting informants (consumers), complemented by field observation and documentation. The results show Circle K implements five promotional mix elements: advertising (posters and TV display), sales promotion (bundling and discounts), personal selling (suggestive selling), public relations (quality standard communication), and direct and digital marketing (social media and member application). Sales promotion is the most dominant and effective element, particularly price-based promotions and bundling which significantly influence consumer purchase decisions. Differentiation is achieved through modern RTE products (kebab, burrito, onigiri), 24-hour service, and two-floor dine-in facilities, yet faces intense competition from FamilyMart with similar positioning. Key challenges include slow promotion rotation, low app adoption, suboptimal promotional visibility, and operational issues such as inadequate air circulation and high staff turnover. Consumer behavior reveals a strong correlation between promotional intensity and loyalty. The study recommends accelerating promotion rotation to at least biweekly, strengthening visual communication, standardizing personal selling procedures, and intensifying app socialization.